Odnosi med organi oblasti v slovenski lokalni samoupravi - Haček, Miro (Družboslovne razprave, 2013)
The paper aims to analyse the relationship between the legislative (municipal council) and executive (mayor, deputy mayor) branches of power in the Slovenian system of local self-government. In the centre lies the role of the mayor, the role of the director of the municipal administration and the role of the municipal council together with the relationship (which has changed significantly in the past two decades) between the mayor and these two bodies. The theoretical anchor of the contribution is the work of Mouritzen and Svara (2002) where the authors categorise ideal models of executive government at the sub-national levels of government and the relations inside the executive. Based on previous empirical research studies, we analyse the functioning of the executive and legislative branches of power and their mutual relations, starting from the assumption that those relations do not correspond to the quite rigidly defined normative frameworks, but in practice often move beyond them.
Keywords: Municipalities; Občine; Mayors; Župani; Municipal government; Občinska uprava; local government; Local self-government; Lokalna samouprava; Legislative power; Zakonodajna oblast; Executive power; Izvršna oblast; Slovenia; Slovenija